Health Supplies Management Strategy in Improving the Quality of Hospital Services - Fitri Amja Yani; Dina Anggreini; Ismi Khoiriyah Maha; Nyak Firzah; Alwi Safriansyah Lubis; Dewi Agustina (PROMOTOR, 2023)
Given the significance of hospitals in the healthcare system, the caliber of hospital medical services has a direct impact on patient health. Optimizing the health supply management system can be used to improve the standard of hospital services. One management concept that concentrates on putting health management into practice is supply management. The administration of health supplies encompasses the following stages: planning, acquiring, storing, distributing, using, and discarding. The purpose of this literature review was to learn more about health supply management techniques that enhance hospital service quality. Finding several papers that satisfied the inclusion criteria was the first step in conducting literature research. Google Scholar is the database source that was used. Citations were drawn from works that were released in the previous five years, from 2018 to 2023. 12 articles that best fit the research title were selected from the total of 22 publications that were found to meet the inclusion criteria. The literature's findings revealed that several hospitals' supply management plans had not been as successful as anticipated. Thus, it has not been possible to improve service quality to the fullest extent possible. This leads one to the conclusion that more improvements in the supply management strategy are necessary to raise the caliber of hospital services.